(untitled) (Research, Society and Development, 2025)
This experience report aims to describe the process of developing a care flowchart to support the healthcare team in managing suicide attempt situations in a socio-educational context, following the PDCA (Plan, Do, Check, Act) methodology. The project was developed in a socio-educational unit in southern Brazil between September and October 2025. In the planning phase, brainstorming meetings were held with the multidisciplinary team to define essential elements, such as the differentiation between ideation and attempt, the roles of professionals, protocols, and communication strategies. In the execution phase, the flowchart was developed in Canva, adopting the Practical Approach to Care Kit model, aligned with institutional practices. In the verification phase, discussion groups and a meeting with management were held to review and validate the content. Finally, in the action phase, the team received training on how to use the tool. Eight professionals participated in the process, including physicians, nurses, nursing technicians, dentists, and oral health technicians. The participatory methodology fostered engagement, recognition of weaknesses in the work process, and the strengthening of a culture of continuous improvement. The result was the implementation of a standardized flowchart, which contributes to safer, more structured, and efficient service for adolescents serving socio-educational measures.